Parent and peer attachment relationships and time perspective in adolescence: Are they related to satisfaction with life?. (March 2016) - Laghi, Fiorenzo; Pallini, Susanna; Baumgartner, Emma; Guarino, Angela; Baiocco, Roberto
The primary aim of this research was to provide evidence about how adolescents' self-reported parent/peer attachment and time perspective relate to their satisfaction with life. A sample of 1211 adolescents completed self-report measures assessing life satisfaction, time perspective, and the perceived quality of parent and peer attachment. Results showed statistically significant relationships among these variables. Boys resulted higher scored than girls in parent trust and satisfaction with life. Girls resulted higher scored than boys in parent alienation, peer communication, and negative past. Parent and peer attachment predicted satisfaction with life, although the variance explained by peer attachment was low. Negative Past, Hedonistic Present, and Future were signiﬁcantly associated with satisfaction with life in the expected directions. The present study has important implications for future empirical investigation and for clinical intervention.